CONCEPT OF UMMATAN WASATAN IN THE QUR’AN (COMPARATIVE STUDIES OF TAFSĪR AL-MARĀGHĪ AND TAFSĪR AL-QUR’ĀN BI AL-IMLĀ’ BY KH. ZAINI ABDUL MUN’IM) - Mun’im, A. Rafiq Zainul; Fadhila, Fadhila (Universitas Nurul Jadid, 2021)
This study discusses the interpretation of KH. Zaini Mun’im and Ahmad Mustafā al-Marāghī regarding the ummatan wasatan. This research is based on the problem that the interpretation of KH. Zaini Mun’im has the same method and data presentation, and was written at relatively the same time. Besides that, there is an assumption that KH. Zaini Mun’im has a similarity with the tafsīr al-Marāghī. By using the tafsīr muqāran method and tracing the works of both interpretations, Tafsīr bi al-Imlā ‘and Tafsīr al-Marāgī, this article concludes that: first, in terms of data presentation, the interpretation of KH. Zaini Mun’im shares similarities with Tafsir al-Marāghī, and in some cases KH. Zaini Mun’im took al-Maraghi’s opinion. However, the two of them differ in commenting on cases developing in their communities. When interpreting the Koran, KH. Zaini Mun’im always associated with Indonesian traditions and culture, especially the pesantren tradition. Second, when interpreting the wasatan ummatan, both KH. Zaini Mun’im and Ahmad Mustafa al-Marāghi have significant differences. For KH. Zaini, ummatan wasatan is not only a moderate ummah as stated by Ahmad Mustafā al-Marāghī, but these moderate values must be based on al-Qur’an and hadith. This research also confirms that an interpretation, although in some cases taking the opinion of previous scholars, reflects the spirit of the times and traditions.